A copper oxide-doped low-resistance tin antimony oxide target and preparation method thereof

By doping copper oxide and adopting a specific preparation method, the problems of high resistivity and poor uniformity of traditional tin oxide antimony targets are solved, and the preparation of low-resistance tin oxide antimony targets are realized, with the resistivity difference being less than 3.3mΩ.cm.

CN119774999APending Publication Date: 2025-04-08ANHUI DIRAC NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411777250.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional tin oxide antimony targets have high resistivity and poor resistivity uniformity.

Method used

Low resistance tin oxide antimony targets are prepared by doping copper oxide and adopting specific preparation methods including premixing, grinding, spray drying, cold isostatic molding and multi-stage degreasing sintering.

Benefits of technology

The resistivity of tin oxide antimony target material is effectively reduced, with the resistivity difference being less than 3.3mΩ.cm, and the sintering density and application range of the target material are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of target materials, and in particular to a low-resistance antimony tin oxide target doped with copper oxide and a preparation method thereof, wherein the target material comprises the following raw materials in parts by weight: 97-98 parts of tin oxide, 1-3 parts of antimony oxide, 1-3 parts of copper oxide, 0.5-1 parts of a binder, and 0.2-0.5 parts of a plasticizer. The preparation method comprises the steps of pulping, granulation, molding, sintering, and the like. The present invention can effectively increase the uniformity of antimony oxide and copper oxide in the base tin oxide through two sandings, and effectively improve the disadvantage of poor uniformity of resistivity of antimony tin oxide target. Through reasonable formulation, process flow, and parameter setting, the problem of high resistivity of traditional antimony tin oxide target can be solved, and the resistivity difference is less than 3.3mΩ.cm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of target materials, and in particular to a copper oxide-doped low-resistance tin antimony oxide target material and a preparation method thereof. Background Art

[0002] ITO targets are widely used in display, touch, low-e glass and other industries. With the development of the photovoltaic industry in recent years, the existing indium content has been rapidly consumed. For the sustainable development of the photovoltaic industry, materials are urgently needed to replace ITO ceramic targets.

[0003] The resistivity of the target material is highly correlated with the square resistance of the solar cell after coating. The electron mobility of the low-resistance target material after coating is often higher than that of the high-resistance target material. Antimony tin oxide ceramic material is a wide-bandgap semiconductor material with a direct bandgap, good chemical, mechanical and thermal stability, and is a potential alternative to ITO target materials. However, the traditional antimony tin oxide target material has a high resistivity (usually 500-1000mΩ.cm), a high average resistivity, and large differences in resistance at different points on the target material. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a copper oxide-doped low-resistance tin antimony oxide target and a preparation method thereof, so as to solve the problem of high resistivity of traditional tin antimony oxide targets.

[0005] Based on the above purpose, the present invention provides a low-resistance tin antimony oxide target doped with copper oxide. The preparation of the target includes the following raw materials in parts by weight: 97-98 parts of tin oxide, 1-3 parts of antimony oxide, 1-3 parts of copper oxide, 0.5-1 parts of binder and 0.2-0.5 parts of plasticizer.

[0006] The tin oxide powder has a purity of ≥99.99% and a specific surface area of ​​10-15m 2 / g; the purity of antimony oxide powder is ≥99.99%, and the specific surface area is 10-13m 2 / g; the purity of copper oxide powder is ≥99.99%, and the specific surface area is 10-13m 2 / g.

[0007] The method for preparing the copper oxide-doped low-resistance tin antimony oxide target comprises the following steps:

[0008] S1. Antimony oxide and copper oxide are weighed according to the formula, pre-mixed with ultrapure water, and then ground. Zirconia beads of Φ0.2-0.3 mm are used as grinding media to obtain slurry 1.

[0009] S2, taking tin oxide according to the formula and adding ultrapure water to premix and grinding, using zirconium oxide beads of Φ0.45-0.55 mm as grinding media to obtain slurry 2;

[0010] S3, adding slurry 1 to slurry 2 and continuing grinding, then adding 0.2-0.5% of a binder and 0.2-0.5% of a plasticizer to obtain a mixed slurry;

[0011] S4, introducing the mixed slurry into a spray dryer for spray granulation to obtain tin antimony oxide granules;

[0012] S5, cold isostatic pressing the antimony tin oxide pellets to obtain antimony tin oxide green bodies;

[0013] S6, placing the antimony tin oxide green body in a normal pressure atmosphere sintering furnace for degreasing and sintering to obtain an antimony tin oxide target.

[0014] The parameters of the debinding sintering are as follows:

[0015] The first heating stage: 7-9 hours, the room temperature rises to 400-600℃, and compressed air is introduced at a flow rate of 10-30L / min;

[0016] The first insulation stage: 2-3 hours, 400-600℃ insulation, compressed air flow rate of 10-50L / min;

[0017] The second heating stage: 3-5 hours, heating to 750-800℃, introducing compressed air with a flow rate of 20-30L / min;

[0018] The third heating stage: 10-15 hours, heating to 1400-1600℃, introducing oxygen at a flow rate of 10-30L / min;

[0019] Second insulation stage: 10-20 hours, insulation, oxygen flow, flow rate 10-20L / min;

[0020] Cooling stage: When the temperature reaches 1000℃, stop introducing oxygen and allow the mixture to cool naturally to room temperature.

[0021] The premixing time in S1 is 30-60 minutes, the grinding speed is 400-800 rpm, and the grinding time is 2-4 hours; the premixing time in S2 is 30-60 minutes, the grinding speed is 400-800 rpm, and the grinding time is 2-4 hours.

[0022] The air inlet temperature of the spray drying in S4 is 240-260° C., the air outlet temperature is 100-120° C., and the rotation speed of the centrifugal atomizer is 8000-10000 rpm.

[0023] The antimony tin oxide granules in S4 are screened with an 80-mesh screen to remove large particles, and mixed with a V-type powder mixer.

[0024] The method for cold isostatic pressing the tin oxide antimony granules in S5 is to first load the tin oxide antimony granules into a rubber mold, and then put the rubber mold into a cold isostatic press for compression molding.

[0025] The pressure of the cold isostatic pressing in S5 is 300-600 MPa, and the holding time is 1-10 minutes.

[0026] Preferably, the binder is polyvinyl alcohol and the plasticizer is polyethylene glycol.

[0027] In the S5, a primary molding is performed before the cold isostatic pressing. After the primary molding, the target material is packaged in a composite nylon PE bag with a single-side thickness of 0.2-0.4 mm, and the excess air in the PE bag is removed by a vacuum packaging machine. The pressure of the primary molding is 90-100 MPa, and the time is 5-8 minutes. The two moldings and the setting of the corresponding process parameters help the target material to withstand thermal stress and improve the life and application range of the target material.

[0028] Beneficial effects of the present invention: The present invention can effectively increase the uniformity of antimony oxide and copper oxide in the base tin oxide through two sandings, and effectively improve the disadvantage of poor resistivity uniformity of tin antimony oxide target. Through reasonable formulation, process flow and parameter setting, the problem of high resistivity of traditional tin antimony oxide target can be solved, and the resistivity difference is less than 3.3mΩ.cm. During the degreasing and sintering stage of the target material of the present invention, it is kept warm at a suitable heating rate, and through multi-stage heating and insulation, the process of target micro-grains forming, growing and breaking is carried out to improve the sintering density. During the target material cooling stage, the internal stress of the target material will be released outward from the inside of the target material to maintain the better internal structure of the target material. DETAILED DESCRIPTION

[0029] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0030] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The words "first", "second" and similar words used in the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. The words "include" or "comprise" and similar words mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0031] Example 1

[0032] Weigh 9700g of tin oxide powder, 155g of antimony oxide powder and 145g of copper oxide powder. The powder properties meet the requirements and are set aside.

[0033] The method for preparing the copper oxide-doped low-resistance antimony tin oxide target of this embodiment comprises the following steps:

[0034] S1. Pour 5 kg of ultrapure water into the slurry barrel, put the weighed antimony oxide and copper oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with a sand mill 1, use φ0.3 mm zirconium oxide beads as the grinding medium, and grind the mixture at a speed of 600 rpm for 3 hours to obtain a precursor slurry 1;

[0035] S2, inject 25kg of ultrapure water into the slurry barrel, put the weighed tin oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with sand mill 2, use φ0.5mm zirconium oxide beads as grinding media, sand mill 1 with a speed of 600rpm, grind for 30 minutes to obtain precursor slurry 2; put precursor 1 into precursor 2, continue grinding for 3 hours to obtain slurry 3;

[0036] S3. Inject 60 g of binder polyvinyl alcohol and 20 g of plasticizer polyethylene glycol into slurry 3, and continue grinding for 30 minutes to obtain antimony tin oxide slurry.

[0037] S4. The antimony tin oxide slurry is introduced into a spray dryer for spray granulation to obtain antimony tin oxide granules. The speed of the centrifugal atomizer is 9000 rpm, the air inlet temperature is 240°C, and the air outlet temperature is 100°C to obtain granules 1. The large particles of granules 1 are sieved out with an 80-mesh screen to obtain granules 2, and granules 2 are mixed with a V-type powder mixer for 30 minutes.

[0038] S5, the pellets 2 are loaded into a rubber mold, the pellets in the mold are vibrated with a vibrator, and the mold is put into a cold isostatic press to form a green body of antimony tin oxide. The cold isostatic press pressure is 400 MPa, and the holding time is 5 minutes.

[0039] S6. Degrease and sinter the pressed tin antimony oxide target at normal pressure, raise the temperature from room temperature to 500°C evenly in 8 hours, during which CDA (compressed air) is continuously introduced into the sintering furnace; keep it at 500°C for 2 hours, during which CDA is introduced; raise the temperature from 500°C to 800°C evenly in 4 hours, during which CDA is introduced; raise the temperature to 1450°C evenly in 12 hours, during which oxygen is introduced into the sintering furnace, and the oxygen concentration is ≥99%; keep it at 1450°C for 15 hours, during which oxygen is introduced into the sintering furnace; turn off the power of the sintering furnace to cool it down, stop introducing oxygen when the temperature reaches 1000°C, and take it out of the furnace after it naturally cools to room temperature.

[0040] The resistivity of the target material was tested at four points on the antimony tin oxide target material obtained in this embodiment, and the results were 7.4 mΩ.cm, 6.8 mΩ.cm, 5.5 mΩ.cm, and 8.2 mΩ.cm, respectively. The average resistivity value ρ was 6.9 mΩ.cm, and the resistivity difference ρmax-ρmin=2.7 mΩ.cm.

[0041] Example 2

[0042] Weigh 9800g of tin oxide powder, 100g of antimony oxide powder and 100g of copper oxide powder. The properties of the powders meet the requirements and are set aside.

[0043] The method for preparing the copper oxide-doped low-resistance antimony tin oxide target of this embodiment comprises the following steps:

[0044] S1. Pour 4.5 kg of ultrapure water into the slurry barrel, put the weighed antimony oxide and copper oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with a sand mill 1, use φ0.3 mm zirconium oxide beads as the grinding medium, and grind the mixture at a speed of 600 rpm for 3 hours to obtain a precursor slurry 1;

[0045] S2, inject 25.5 kg of ultrapure water into the slurry barrel, put the weighed tin oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with sand mill 2, use φ0.5 mm zirconium oxide beads as grinding media, sand mill 1 with a speed of 600 rpm, grind for 30 minutes to obtain precursor slurry 2; put precursor 1 into precursor 2, continue grinding for 3 hours to obtain slurry 3;

[0046] S3. Inject 80 g of binder polyvinyl alcohol and 40 g of plasticizer polyethylene glycol into slurry 3, and continue grinding for 30 min to obtain antimony tin oxide slurry.

[0047] S4. The antimony tin oxide slurry is introduced into a spray dryer for spray granulation to obtain antimony tin oxide granules. The speed of the centrifugal atomizer is 9000 rpm, the air inlet temperature is 240°C, and the air outlet temperature is 100°C to obtain granules 1. The large particles of granules 1 are sieved out with an 80-mesh screen to obtain granules 2, and granules 2 are mixed with a V-type powder mixer for 30 minutes.

[0048] S5, the pellets 2 are loaded into a rubber mold, the pellets in the mold are vibrated with a vibrator, and the mold is put into a cold isostatic press to form a green body of antimony tin oxide. The cold isostatic press pressure is 400 MPa, and the holding time is 5 minutes.

[0049] S6. Degrease and sinter the pressed tin antimony oxide target at normal pressure, raise the temperature from room temperature to 500°C evenly in 8 hours, during which CDA is continuously introduced into the sintering furnace; keep it at 500°C for 2 hours, during which CDA is introduced; raise the temperature from 500°C to 800°C evenly in 4 hours, during which CDA is introduced; raise the temperature to 1450°C evenly in 12 hours, during which oxygen is introduced into the sintering furnace, and the oxygen concentration is ≥99%; keep it at 1450°C for 15 hours, during which oxygen is introduced into the sintering furnace; turn off the power of the sintering furnace to cool it down, stop introducing oxygen when the temperature reaches 1000°C, and take it out of the furnace after it naturally cools to room temperature.

[0050] The resistivity of the target material was tested at four points on the antimony tin oxide target material obtained in this embodiment, and the results were 20.5 mΩ.cm, 17.6 mΩ.cm, 18.5 mΩ.cm, and 17.2 mΩ.cm, respectively. The average resistivity value ρ was 18.5 mΩ.cm, and the resistivity difference ρmax-ρmin=3.3 mΩ.cm.

[0051] Example 3

[0052] Weigh 9750g of tin oxide powder, 100g of antimony oxide powder and 150g of copper oxide powder. If the properties of the powders meet the requirements, set them aside.

[0053] The method for preparing the copper oxide-doped low-resistance antimony tin oxide target of this embodiment comprises the following steps:

[0054] S1. Pour 4.5 kg of ultrapure water into the slurry barrel, put the weighed antimony oxide and copper oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with a sand mill 1, use φ0.3 mm zirconium oxide beads as the grinding medium, and grind the mixture at a speed of 600 rpm for 3 hours to obtain a precursor slurry 1;

[0055] S2, inject 25.5 kg of ultrapure water into the slurry barrel, put the weighed tin oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with sand mill 2, use φ0.5 mm zirconium oxide beads as grinding media, sand mill 1 with a speed of 600 rpm, grind for 30 minutes to obtain precursor slurry 2; put precursor 1 into precursor 2, continue grinding for 3 hours to obtain slurry 3;

[0056] S3. Inject 70 g of binder polyvinyl alcohol and 30 g of plasticizer polyethylene glycol into slurry 3, and continue grinding for 30 min to obtain antimony tin oxide slurry.

[0057] S4. The antimony tin oxide slurry is introduced into a spray dryer for spray granulation to obtain antimony tin oxide granules. The speed of the centrifugal atomizer is 9000 rpm, the air inlet temperature is 240°C, and the air outlet temperature is 100°C to obtain granules 1. The large particles of granules 1 are sieved out with an 80-mesh screen to obtain granules 2, and granules 2 are mixed with a V-type powder mixer for 30 minutes.

[0058] S5, the pellets 2 are loaded into a rubber mold, the pellets in the mold are vibrated with a vibrator, and the mold is put into a cold isostatic press to form a green body of antimony tin oxide. The cold isostatic press pressure is 400 MPa, and the holding time is 5 minutes.

[0059] S6. Degrease and sinter the pressed tin antimony oxide target at normal pressure, raise the temperature from room temperature to 500°C evenly in 8 hours, during which CDA is continuously introduced into the sintering furnace; keep it at 500°C for 2 hours, during which CDA is introduced; raise the temperature from 500°C to 800°C evenly in 4 hours, during which CDA is introduced; raise the temperature to 1450°C evenly in 12 hours, during which oxygen is introduced into the sintering furnace, and the oxygen concentration is ≥99%; keep it at 1450°C for 15 hours, during which oxygen is introduced into the sintering furnace; turn off the power of the sintering furnace to cool it down, stop introducing oxygen when the temperature reaches 1000°C, and take it out of the furnace after it naturally cools to room temperature.

[0060] The resistivity of the target material was tested at four points on the antimony tin oxide target material obtained in this embodiment, and the results were 5.8 mΩ.cm, 5.6 mΩ.cm, 7.2 mΩ.cm, and 8.1 mΩ.cm, respectively. The average resistivity value ρ was 6.7 mΩ.cm, and the resistivity difference ρmax-ρmin=2.7 mΩ.cm.

[0061] Example 4

[0062] Weigh 9750g of tin oxide powder, 100g of antimony oxide powder and 150g of copper oxide powder. If the properties of the powders meet the requirements, set them aside.

[0063] The method for preparing the copper oxide-doped low-resistance antimony tin oxide target of this embodiment comprises the following steps:

[0064] S1. Pour 4.5 kg of ultrapure water into the slurry barrel, put the weighed antimony oxide and copper oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with a sand mill 1, use φ0.3 mm zirconium oxide beads as the grinding medium, and grind the mixture at a speed of 600 rpm for 3 hours to obtain a precursor slurry 1;

[0065] S2, inject 25.5 kg of ultrapure water into the slurry barrel, put the weighed tin oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with sand mill 2, use φ0.5 mm zirconium oxide beads as grinding media, sand mill 1 with a speed of 600 rpm, grind for 30 minutes to obtain precursor slurry 2; put precursor 1 into precursor 2, continue grinding for 3 hours to obtain slurry 3;

[0066] S3. Inject 90 g of binder polyvinyl alcohol and 40 g of plasticizer polyethylene glycol into slurry 3, and continue grinding for 30 min to obtain antimony tin oxide slurry.

[0067] S4. The antimony tin oxide slurry is introduced into a spray dryer for spray granulation to obtain antimony tin oxide granules. The speed of the centrifugal atomizer is 9000 rpm, the air inlet temperature is 240°C, and the air outlet temperature is 100°C to obtain granules 1. The large particles of granules 1 are sieved out with an 80-mesh screen to obtain granules 2, and granules 2 are mixed with a V-type powder mixer for 30 minutes.

[0068] S5, the pellets 2 are loaded into a rubber mold, and the pellets in the mold are vibrated with a vibrator, and a pre-pressing molding is performed, the pressure of the first molding is 95MPa, and the time is 6min. After the first molding, the target material is packaged in a composite nylon PE bag with a single-side thickness of 0.3mm, and the excess air in the PE bag is evacuated by a vacuum packaging machine, and then the mold is put into a cold isostatic press to press and mold to obtain antimony tin oxide green body. The cold isostatic pressing pressure is 400Mpa, and the holding time is 5 minutes.

[0069] S6. Degrease and sinter the pressed tin antimony oxide target at normal pressure, raise the temperature from room temperature to 500°C evenly in 8 hours, during which CDA is continuously introduced into the sintering furnace; keep it at 500°C for 2 hours, during which CDA is introduced; raise the temperature from 500°C to 800°C evenly in 4 hours, during which CDA is introduced; raise the temperature to 1450°C evenly in 12 hours, during which oxygen is introduced into the sintering furnace, and the oxygen concentration is ≥99%; keep it at 1450°C for 15 hours, during which oxygen is introduced into the sintering furnace; turn off the power of the sintering furnace to cool it down, stop introducing oxygen when the temperature reaches 1000°C, and take it out of the furnace after it naturally cools to room temperature.

[0070] The resistivity of the antimony tin oxide target obtained in this embodiment was tested at four points, which were 5.5 mΩ.cm, 5.7 mΩ.cm, 6.8 mΩ.cm, and 7.6 mΩ.cm, respectively, with an average resistivity ρ of 6.4 mΩ.cm and a resistivity difference ρmax-ρmin=2.1 mΩ.cm. It was also found that the antimony tin oxide target in this embodiment had a relative density of up to 98.25%, which was 2.62% higher than the relative density of the antimony tin oxide target obtained in Example 3.

[0071] Comparative Example 1

[0072] Weigh 9700g of tin oxide powder and 300g of antimony oxide powder. If the properties of the powders meet the requirements, set them aside.

[0073] Pour 4.5 kg of ultrapure water into the slurry barrel, add the weighed antimony oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with a sand mill 1, use φ0.3 mm zirconium oxide beads as the grinding medium, and grind the mixture at a speed of 600 rpm for 3 hours to obtain a precursor slurry 1;

[0074] Pour 25.5 kg of ultrapure water into the slurry barrel, put the weighed tin oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed liquid with sand mill 2, use φ0.5 mm zirconium oxide beads as the grinding medium, and grind the mixture at a speed of 600 rpm for 30 minutes to obtain precursor slurry 2; put precursor 1 into precursor 2, and continue grinding for 3 hours to obtain slurry 3;

[0075] 80 g of binder polyvinyl alcohol and 40 g of plasticizer polyethylene glycol were injected into slurry 3, and grinding was continued for 30 minutes to obtain tin antimony oxide slurry.

[0076] The above antimony tin oxide slurry was introduced into a spray dryer for spray granulation to obtain antimony tin oxide granules. The speed of the centrifugal atomizer was 9000 rpm, the inlet air temperature was 240°C, and the outlet air temperature was 100°C to obtain granules 1.

[0077] The large particles of Granule 1 were sieved out with an 80-mesh screen to obtain Granule 2, which was then mixed with a V-type mixer for 30 minutes.

[0078] The above pellets 2 are placed in a rubber mold, the pellets in the mold are vibrated with a vibrator, and the mold is then placed in a cold isostatic press to form a green body of antimony tin oxide. The cold isostatic press pressure is 400 MPa, and the holding time is 5 minutes.

[0079] The pressed tin antimony oxide target is degreased and sintered at normal pressure, and the temperature is uniformly increased from room temperature to 500°C in 8 hours, during which CDA is continuously introduced into the sintering furnace; it is kept at 500°C for 2 hours, during which CDA is introduced; the temperature is uniformly increased from 500°C to 800°C in 4 hours, during which CDA is introduced; the temperature is uniformly increased to 1450°C in 12 hours, and oxygen is introduced into the sintering furnace during the heating period, and the oxygen concentration is ≥99%; it is kept at 1450°C for 15 hours, during which oxygen is introduced into the sintering furnace; the sintering furnace power is turned off to cool down, and the temperature is about to reach 1000°C, and the oxygen is stopped, and it is naturally cooled to room temperature before being taken out of the furnace.

[0080] The resistivity of the target material was tested at four points on the antimony tin oxide target material obtained in this comparative example, and the results were 800 mΩ.cm, 450 mΩ.cm, 320 mΩ.cm, and 640 mΩ.cm, respectively. The average resistivity value ρ was 552.5 mΩ.cm, and the resistivity difference ρmax-ρmin=480 mΩ.cm.

[0081] Comparative Example 2

[0082] Weigh 9750g of tin oxide powder and 250g of antimony oxide powder. If the properties of the powders meet the requirements, set aside.

[0083] 5 kg of ultrapure water was injected into the slurry barrel, and the weighed antimony oxide powder was added into the slurry barrel for premixing for 45 minutes. The mixed solution was ground by a sand mill 1, and the grinding medium was φ0.3 mm zirconium oxide beads. The speed of the sand mill 1 was 600 rpm, and the precursor slurry 1 was obtained by grinding for 3 hours.

[0084] Pour 25 kg of ultrapure water into the slurry barrel, put the weighed tin oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with sand mill 2, use φ0.5 mm zirconium oxide beads as grinding media, and grind the mixture at a speed of 600 rpm for 30 minutes to obtain precursor slurry 2; put precursor 1 into precursor 2, and continue grinding for 3 hours to obtain slurry 3;

[0085] 90 g of polyvinyl alcohol as a binder and 30 g of polyethylene glycol as a plasticizer were injected into slurry 3, and grinding was continued for 30 minutes to obtain antimony tin oxide slurry.

[0086] The above antimony tin oxide slurry was introduced into a spray dryer for spray granulation to obtain antimony tin oxide granules. The speed of the centrifugal atomizer was 9000 rpm, the inlet air temperature was 240°C, and the outlet air temperature was 100°C to obtain granules 1.

[0087] The large particles of Granule 1 were sieved out with an 80-mesh screen to obtain Granule 2, which was then mixed with a V-type mixer for 30 minutes.

[0088] The above pellets 2 are placed in a rubber mold, the pellets in the mold are vibrated with a vibrator, and the mold is then placed in a cold isostatic press to form a green body of antimony tin oxide. The cold isostatic press pressure is 400 MPa, and the holding time is 5 minutes.

[0089] The pressed tin antimony oxide target is degreased and sintered at normal pressure, and the temperature is uniformly increased from room temperature to 500°C in 8 hours, during which CDA is continuously introduced into the sintering furnace; it is kept at 500°C for 2 hours, during which CDA is introduced; the temperature is uniformly increased from 500°C to 800°C in 4 hours, during which CDA is introduced; the temperature is uniformly increased to 1450°C in 12 hours, and oxygen is introduced into the sintering furnace during the heating period, and the oxygen concentration is ≥99%; it is kept at 1450°C for 15 hours, during which oxygen is introduced into the sintering furnace; the sintering furnace power is turned off to cool down, and the temperature is about to reach 1000°C, and the oxygen is stopped, and it is naturally cooled to room temperature before being taken out of the furnace.

[0090] The resistivity of the target material was tested at four points on the antimony tin oxide target obtained in this comparative example, which were 750 mΩ.cm, 624 mΩ.cm, 432 mΩ.cm, and 544 mΩ.cm, respectively. The average resistivity ρ was 587.5 mΩ.cm, and the resistivity difference ρmax-ρmin=318 mΩ.cm.

[0091] Comparative Example 3

[0092] Weigh 9800g of tin oxide powder and 200g of antimony oxide powder. If the properties of the powders meet the requirements, set them aside.

[0093] 5 kg of ultrapure water was injected into the slurry barrel, and the weighed antimony oxide powder was added into the slurry barrel for premixing for 45 minutes. The mixed solution was ground by a sand mill 1, and the grinding medium was φ0.3 mm zirconium oxide beads. The speed of the sand mill 1 was 600 rpm, and the precursor slurry 1 was obtained by grinding for 3 hours.

[0094] Pour 25 kg of ultrapure water into the slurry barrel, put the weighed tin oxide powder into the slurry barrel and premix for 45 minutes, grind the mixed solution with sand mill 2, use φ0.5 mm zirconium oxide beads as grinding media, and grind the mixture at a speed of 600 rpm for 30 minutes to obtain precursor slurry 2; put precursor 1 into precursor 2, and continue grinding for 3 hours to obtain slurry 3;

[0095] 70 g of binder polyvinyl alcohol and 30 g of plasticizer polyethylene glycol were injected into slurry 3, and grinding was continued for 30 minutes to obtain tin antimony oxide slurry.

[0096] The above antimony tin oxide slurry was introduced into a spray dryer for spray granulation to obtain antimony tin oxide granules. The speed of the centrifugal atomizer was 9000 rpm, the inlet air temperature was 240°C, and the outlet air temperature was 100°C to obtain granules 1.

[0097] The large particles of Granule 1 were sieved out with an 80-mesh screen to obtain Granule 2, which was then mixed with a V-type mixer for 30 minutes.

[0098] The above pellets 2 are placed in a rubber mold, the pellets in the mold are vibrated with a vibrator, and the mold is then placed in a cold isostatic press to form a green body of antimony tin oxide. The cold isostatic press pressure is 400 MPa, and the holding time is 5 minutes.

[0099] The pressed tin antimony oxide target is degreased and sintered at normal pressure, and the temperature is uniformly increased from room temperature to 500°C in 8 hours, during which CDA is continuously introduced into the sintering furnace; it is kept at 500°C for 2 hours, during which CDA is introduced; the temperature is uniformly increased from 500°C to 800°C in 4 hours, during which CDA is introduced; the temperature is uniformly increased to 1450°C in 12 hours, and oxygen is introduced into the sintering furnace during the heating period, and the oxygen concentration is ≥99%; it is kept at 1450°C for 15 hours, during which oxygen is introduced into the sintering furnace; the sintering furnace power is turned off to cool down, and the temperature is about to reach 1000°C, and the oxygen is stopped, and it is naturally cooled to room temperature before being taken out of the furnace.

[0100] The resistivity of the target material was tested at four points on the antimony tin oxide target material obtained in this comparative example, and the results were 458 mΩ.cm, 659 mΩ.cm, 369 mΩ.cm, and 579 mΩ.cm, respectively. The average resistivity value ρ was 516 mΩ.cm, and the resistivity difference ρmax-ρmin=290 mΩ.cm.

[0101] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A low-resistance antimony tin oxide target doped with copper oxide, characterized in that: The target material is prepared by mixing the following raw materials in parts by weight: 97-98 parts of tin oxide, 1-3 parts of antimony oxide, 1-3 parts of copper oxide, 0.5-1 parts of a binder and 0.2-0.5 parts of a plasticizer.

2. The low-resistance antimony tin oxide target doped with copper oxide according to claim 1, characterized in that: The tin oxide powder has a purity of ≥99.99% and a specific surface area of ​​10-15m 2 / g; the purity of antimony oxide powder is ≥99.99%, and the specific surface area is 10-13m 2 / g; the purity of copper oxide powder is ≥99.99%, and the specific surface area is 10-13m 2 / g.

3. The method for preparing a low-resistance antimony tin oxide target doped with copper oxide according to claim 1 or 2, characterized in that: The steps include: S1. Antimony oxide and copper oxide are weighed according to the formula, pre-mixed with ultrapure water, and then ground. Zirconia beads of Φ0.2-0.3 mm are used as grinding media to obtain slurry 1. S2, taking tin oxide according to the formula and adding ultrapure water to premix and grinding, using zirconium oxide beads of Φ0.45-0.55 mm as grinding media to obtain slurry 2; S3, adding slurry 1 to slurry 2 and continuing grinding, and then adding a binder and a plasticizer to obtain a mixed slurry; S4, introducing the mixed slurry into a spray dryer for spray granulation to obtain tin antimony oxide granules; S5, cold isostatic pressing the antimony tin oxide pellets to obtain antimony tin oxide green bodies; S6, placing the antimony tin oxide green body in a normal pressure atmosphere sintering furnace for degreasing and sintering to obtain an antimony tin oxide target.

4. The method for preparing the copper oxide-doped low-resistance antimony tin oxide target according to claim 3, characterized in that: The parameters of the debinding sintering are as follows: The first heating stage: 7-9 hours, the room temperature rises to 400-600℃, and compressed air is introduced at a flow rate of 10-30L / min; The first insulation stage: 2-3 hours, 400-600℃ insulation, compressed air flow rate of 10-50L / min; The second heating stage: 3-5 hours, heating to 750-800℃, introducing compressed air with a flow rate of 20-30L / min; The third heating stage: 10-15 hours, heating to 1400-1600℃, introducing oxygen at a flow rate of 10-30L / min; Second insulation stage: 10-20 hours, insulation, oxygen flow, flow rate 10-20L / min; Cooling stage: When the temperature reaches 1000℃, stop introducing oxygen and allow the mixture to cool naturally to room temperature.

5. The method for preparing the copper oxide-doped low-resistance antimony tin oxide target according to claim 3, characterized in that: The premixing time in S1 is 30-60 minutes, the grinding speed is 400-800 rpm, and the grinding time is 2-4 hours; the premixing time in S2 is 30-60 minutes, the grinding speed is 400-800 rpm, and the grinding time is 2-4 hours.

6. The method for preparing the copper oxide-doped low-resistance antimony tin oxide target according to claim 3, characterized in that: The air inlet temperature of the spray drying in S4 is 240-260° C., the air outlet temperature is 100-120° C., and the rotation speed of the centrifugal atomizer is 8000-10000 rpm.

7. The method for preparing the copper oxide-doped low-resistance antimony tin oxide target according to claim 3, characterized in that: The antimony tin oxide granules in S4 are screened with an 80-mesh screen to remove large particles, and mixed with a V-type powder mixer.

8. The method for preparing the copper oxide-doped low-resistance antimony tin oxide target according to claim 3, characterized in that: The method for cold isostatic pressing the tin oxide antimony granules in S5 is to first load the tin oxide antimony granules into a rubber mold, and then put the rubber mold into a cold isostatic press for compression molding.

9. The method for preparing a low-resistance antimony tin oxide target doped with copper oxide according to claim 3, characterized in that: The pressure of the cold isostatic pressing in S5 is 300-600 MPa, and the holding time is 1-10 minutes.